HUMAN HERPESVIRUS 8 AND LYMPHOPROLIFERATIVE DISEASES - Maria Luisa Calabrò; Ronit Sarid (Mediterranean Journal of Hematology and Infectious Diseases)
The spectrum of lymphoproliferative disorders linked to human herpesvirus 8 (HHV-8) infection has been constantly increasing since the discovery of its first etiologic association with primary effusion lymphoma (PEL). PEL is a rapidly progressing non-Hodgkin’s B-cell lymphoma that develops in body cavities in an effusional form. With the increase in the overall survival of PEL patients, as well as the introduction of HHV-8 surveillance in immunocompromised patients, the extracavitary, solid counterpart of PEL was later identified. Moreover, virtually all plasmablastic variants of multicentric Castleman’s disease (MCD) developing in HIV-1-infected individuals harbor HHV-8, providing a strong etiologic link between MCD and this oncogenic herpesvirus. Two other pathological conditions develop in HIV-1-infected persons concomitantly with MCD: MCD with plasmablastic clusters and MCD-associated plasmablastic lymphoma, the first likely representing an intermediate stage preceding the full neoplastic stage. MCD in leukemic phase has also been described, albeit much less commonly. The germinotropic lymphoproliferative disorder (GLPD) may resemble extracavitary PEL, but develops in immune competent HHV8-infected individuals, and, unlike the disorders described above, it responds well to conventional therapies. Almost all HHV-8-mediated lymphoproliferative disorders are the result of an interaction between HHV-8 infection and a dysregulated immunological system, leading to the formation of inflammatory niches in which B cells, at different developmental stages, are infected, proliferate and may eventually shift from a polyclonal state to a monoclonal/neoplastic disorder. Herein, we describe the association between HHV-8 and lymphoproliferative disorders and highlight the predominant distinctive features of each disease.